2019
DOI: 10.1002/ejic.201900198
|View full text |Cite
|
Sign up to set email alerts
|

Apical Cyanide Ligand Substitution in Heterometallic Clusters [Re3Mo3Q8(CN)6]n (Q = S, Se)

Abstract: A number of transition metal cluster compounds can be obtained only in the melt of inorganic cyanides and, therefore, contain terminal cyanide ligands. Substitution of these ligands, which is often necessary to change the physicochemical properties of the clusters, is an urgent problem because of their low reactivity in substitution reactions. In this work, a synthetic approach has been developed for the substitution of CN-ligands in the heterometallic cluster anions [Re 3 Mo 3 Q 8 (CN) 6 ] n-(Q = S, n = 6; Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Such clusters, being combined in a form of solid solutions, may unveil new possibilities for construction of functional materials based on heterometallic clusters. It was previously shown that cyanide apical ligands of [{Re 3 Mo 3 S 8 }(CN) 6 ] 5− cluster, which were considered as inert to substitution in rhenium cluster complexes, can be replaced by 4- tert -butylpyridine 29 maintaining overall structure of complex and gradually change the properties of material.…”
Section: Resultsmentioning
confidence: 99%
“…Such clusters, being combined in a form of solid solutions, may unveil new possibilities for construction of functional materials based on heterometallic clusters. It was previously shown that cyanide apical ligands of [{Re 3 Mo 3 S 8 }(CN) 6 ] 5− cluster, which were considered as inert to substitution in rhenium cluster complexes, can be replaced by 4- tert -butylpyridine 29 maintaining overall structure of complex and gradually change the properties of material.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of non-stoichiometric phases is quite rare in the chemistry of clusters. Heterometallic clusters represent a special type of cluster compounds containing different metal atoms within the core [13][14][15][16][17][18][19][20][21][22][23] . The introduction of another metal atom makes it possible to change the properties of cluster compounds in a controlled manner, and can also lead to interesting optical properties due to a decrease of the symmetry of the cluster core.…”
Section: Introductionmentioning
confidence: 99%